Localization of the spinal nucleus of accessory nerve in the albino rat - Ullah, Muzammil; Mansor, Othman; Ismail, Zul lzhar Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
INTRODUCTION. The spinal nucleus of accessory nerve (SNA, hereafter) is the group( s) of motor neuron somata that supply the sternocleidomastoid (SCM) and trapezius (TRAP) muscles. There are many conflicting views regarding the longitudinal extent and topography of the SNA even 1n the same species. Kitamura & Sakai (1982) and Matesz & Szekely (1983) located the SNA in rat. There is some disagreement among them regarding the longitudinal extent of the SNA and location of its neuron somata. These disagreements prompted the present investigation in rat. AIMS OF TA ~:STUDY. The aims and objectives oft.h.e study were as follows: (1) To investigate the location of the spinal nucleus of accessory nerve in albino rat, (2) to find out its relationship with neighbouring cell columns, and (3) to investigate wit}lin the nucleus, the locations of motor neuron somata supplying the sternocleidomastoid and trapezius muscles. MATERIALS AND METHODS .. 20 Sprague-Dawley rats (12 males, 8 females) were used in the study.The animals were divided into two groups, Group-! and Group-IT. Group-! included 15 rats and Group-IT included 5 rats. In Group-!, the SNA was localized by retrograde axonal transport of HRP (Horseradish peroxidase) technique. In Group II, the SNA was localized by Retrograde degeneration technique using Thionine as stain for Nissl granules. RESULTS AND CONCLUSIONS. 1. Longitudinally, the SNA was located in the caudal part (caudal 0.9 to 1.2 mm) of Medulla oblongata, and the whole lengths of C-1, C-2, C-3, C-4, C-5 and the rostralfourth of C-6 segments of the spinal cord. 2. In the caudal part of the medulla oblongata, the SNA was represented by a group of neuron somata lying immediately ventrolateral to the pyramidal fibres that were passing dorsolaterally after their decussation. 3. In the spinal cord, the motor neuron somata of SNA were located in dorsomedial (DM) and central (CEN) columns at C-1, in DM, CEN and VL (ventrolateral) columns at C-2 and in VL colwnn only at C-3, C-4, C-5 and rostral-fourth ofC-6. 4. The motor neuron somata supplying the SCM were located in the caudal part (caudal 0.9 to 1.2 mm) of medulla oblongata ventrolateral to the- pyramidal fibres that were passing dorsolaterally after their decussation. They were also located in DM & CEN columns at C-1, in DM, CEN & VL columns at C-2 and only in VL column at the rostral three-fourths of C-3. 5. The motor neuron somata of TRAP were located in the ventrolateral column (VL) only in the caudal three-fourths of C-2, in the whole lengths of C-3, C-4 and C-5, and in the rostral fourth ofC-6.